Dramatizing the Nation: Television, History and the Construction of Singaporean Identity - Tay, Jinna (Television Histories in Asia: Issues and Contexts, 2015)
Television dramas, both serials and series, have been a long-term recruiter of large-scale national audiences for television broadcasters as they are potentially able to speak to their audience in affective and imaginative ways (Chan 2011 ; Sun and Gorfi nkel 2014). Usually it is the locally produced drama that resonates most with a national audience, the familiarity of the setting and context often carrying signifi cant implications for social and sometimes political life (Blandford et al. 2011 , Chan 2011 ). These television texts can pick up on popular strands of discourses in the public sphere and succeed in establishing a form of dialogue with audiences; in the instances examined in this chapter, this dialogue is about the formation of national identities or citizenships. There is good reason, then, for broadcasters and governments to attempt to use television drama to educate and persuade, although Sugg and Power ( 2011 : 26-7), long-term drama producers at the BBC World Service Trust, warn that for dramas to succeed in this manner, they first have to be entertaining, otherwise they are unlikely to generate an audience in the fi rst place. Audiences are not easily fooled and can sniff out the difference between being entertained and being preached at in a didactic way. This chapter deals with a period in the history of Singapore where television historical drama played a signifi cant role in creating a national past upon which the promotion of a distinctive national identity might be based. In addition to a consideration of a selection of drama series themselves, the chapter draws upon interviews where viewers are encouraged to share their memories of these dramas, and the part they played in the construction of a Singaporean identity.
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Singapour (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Let the Contests Begin! ‘Singapore Slings’ into Action: Singapore in the Global Television Format Business - Lim, Tania (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Why is the hit Singapore edition of Who Wants To Be A Millionaire? must-see TV?1. Watch it so that you can hold the ‘hottest topic’ with your friends. 2. So you can be encouraged by the courage of some contestants who are bold enough to brave national TV when apparently they have not read enough. 3. So you can judge for yourself if you are bold (and knowledgeable) enough to brave national TV for your possible 1st million. 4. So you can call the number on screen and make your 1st million. 5. Finally, watch it to see for yourself that Singaporeans are not as well read and as globalized as we all think we are.
Num Pages: 17
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Singapour (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Television and Dating in Contemporary China: Identities, Love and Intimacy - Yang, Chao (Palgrave Macmillan Singapore, 2017)
"This book considers the changing nature of intimacy in contemporary China, providing a unique case study of romantic subjectivities in young people in the world's fastest growing economy. Since the implementation of reform in 1978, the economic and socio-cultural environment of modern China has experienced a dramatic transformation under the influence of urbanization and globalization, facilitating more individualized identity among Chinese youth. This book bridges the gap between an emergent emphasis on individualisation and the country's traditional norms and values. It focuses on young people's understandings of various forms of relationships such as cohabitation, extramarital relationships and multiple relationships, suggesting a challenge to traditional familial values and an increasingly diversified understanding of the concepts of love and romance. By examining the formation of relationships among 21st century Chinese youth, notably through the lens of popular Chinese TV dating programs, this book considers how dating and relationships mirror China's changing societal structure and examines social and cultural transformations in Chinese society."
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

The Little Emperors’ New Toys: A Critical Inquiry into Children and Television in China - Zhao, Bin (Springer, 2013)
Drawing on original research I conducted in the late 1980s, the book argues for a critical approach to the study of children and television. It begins with critical reappraisals of previous empiricist and interpretative studies to set the ground for a different theoretical inquiry which links biography with history. The situated activity of children's television viewing therefore has to be related to the broader historical and cultural formations in post-Mao China. By way of a methodological pluralism of questionnaire survey, in-depth interviews and observation, the book provides the reader with a thorough critical analysis of the rise of the new commercial ethic in Chinese society in general, and in the sector of media and communications in particular, at the very historical turning point of the late 1980s. Soon after that, Deng Xiaoping made his significant tour to south China, reckoning a big step forward towards further liberalization and started to form a brave new world in China ever since.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Television in Bangladesh: News and Audiences - Roy, Ratan Kumar (Routledge India, 2020)
This book examines the role of 24/7 television news channels in Bangladesh. By using a multi-sited ethnography of television news media, it showcases the socio-political undercurrents of media practices and the everydayness of TV news in Bangladesh. It discusses a wide gamut of issues such as news making; localised public sphere; audience reaction and viewing culture; impact of rumours and fake news; socio-political conditions; protest mobilization; newsroom politics and perspectives from the ground. An important intervention in the subject, this book will be useful to scholars and researchers of media studies, journalism and mass communication, anthropology, cultural studies, political sociology, political science, sociology, South Asian studies, as well as television professionals, journalists, civil society activists, and those interested in the study of Bangladesh.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Bangladesh (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves - Çetin, Berfin Emre (Cambridge Scholars Publisher, 2015)
The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves explores the representation and reception of nationalism and masculinity in Turkey through an examination of the popular television serial, Valley of the Wolves which has been aired on Turkish television since 2003. This detailed examination of the show demonstrates a particular discourse of nationalism, namely the Turkish Islam synthesis embedded in a gender-specific regime in which the paramilitary hero is placed at the centre. The study draws on thirty-seven in-depth interviews with viewers of the programme from different social backgrounds. These viewers read the serial from various perspectives in the light of their gendered experiences, suggesting that the relationship between text and audience is not necessarily predetermined by the former, but is rather constructed through an interdiscursive process. The book also examines the pleasures of the “contesting” readers of Valley of the Wolves, drawing on the audience interviews, and argues that critical approaches to a particular media text do not present a barrier to audience pleasures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Revisiting the Unplugged Margins: Rural Television Audiences and Mediatization - Türkoğlu, Nurçay (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter examines the social transformation of the television audience of rural Turkey. Villages near a metropolitan area, which were subject to an administrative decision to be relocated, were the focus of my fieldwork 30 years ago. Several visits between 1987 and 2019 to the same location, which is inhabited by television viewers and non-viewers alike, yielded an insightful mapping of engagement with popular culture via television at the periphery in Turkey from a historical perspective. While rural inhabitants are busy with daily labor in the countryside and are not keen on watching television, they are nonetheless aware of and connected to new, nationwide cultural trends and social changes. By reflexively discussing these experiences in ethnographic fieldwork on television habits and reception in rural Turkey over a 30-year span, I avoid the traps of modern-traditional and urban-rural binaries, allowing for an exploration of the role of television in mediating social change in the rural context and thus an analysis of the various complex layers and processes of mediatization among rural audiences.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

The Social and Political Dimensions of Global Television Formats: Reality Television in Lebanon and Saudi Arabia - Kraidy, Marwan (Global Television Formats: Understanding Television Across Borders, 2012)
When scholars and policy makers contemplate the Arab “media revolution,” they mostly think of Al-Jazeera and its news competitors. They are guided by the assumption that all-news satellite television networks are the predominant, even the single, shaper of the Arab public sphere, a perspective exacerbated by the September 11, 2001 attacks. Drawing on a larger work (Kraidy, 2009, forthcoming), this chapter presents an alternative view, emphasizing instead the combined impact of Arab entertainment television and small media such as mobile phones on Arab governance. It explores how entertainment television is an active contributor to shaping what Arab publics discuss and do in both the social and political realms. As local (in this case regional/pan-Arab, reaching two dozen Arabic-speaking countries) adaptations of global television formats, Arab reality television shows exhibit a combination of signs and practices from several worldviews. As such, this chapter will show how Arab reality shows are open to multiple processes of appropriation and redeployment. Though numerous scholars have for years studied the differentiated “reception” of television texts in various contexts, this chapter focuses speciﬁcally on television formats in a context of growing media convergence and protracted political instability and social upheaval. Speciﬁcally, it focuses on reality television’s social and political impact, which stems primarily from its activation of new communication processes between a variety of information and media technologies creating what I call “hypermedia space.” In the new Arab information order, reality television activates hypermedia space because it promotes participatory practices like voting, campaigning and alliance building, via mobile telephones and related devices.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Arabie Saoudite (corpus analysé); Liban (corpus analysé); Qatar (lieu de production du savoir); _Nettoyé

Is the Video Game a Cultural Vehicle? - Chen, Chi-Ying (Games and Culture, 2013)
Following the exportation of Japanese media products such as TV dramas, Japanese culture and products have swept across many Asian countries, especially Taiwan. Based on the historical background and unique characteristics of games, this study investigates the cultural effect of Japanese video games on players in Taiwan. This study also presents an analysis of the differences between TV and the video game as cultural vehicles. We used both quantitative and qualitative methods. Results indicate a relationship between game-playing behavior and the identification of Japanese culture. However, the relationship between video game playing and consumption was nonsignificant. This shows the power of video games in nation-building but not in nation-branding, in contrast with TV. This study presents a discussion of the findings to shed light on the cultural effects of video games.
Keywords: 1-Jeux vidéo; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À nettoyer; _À vérifier-Télé

The International Encyclopedia of Media Studies: Media History and the Foundations of Media Studies - Valdivia, Angharad N.; Nerone, John C.; Mayer, Vicki; Mazzarella, Sharon R.; Parameswaran, Radhika E.; Scharrer, Erica; Darling-Wolf, Fabienne; Gates, Kelly (Wiley-Blackwell, 2013)
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

GSI Adda Talk #2 Riko Banerjee What is it like to be a Gamer or pursue Game Studies in India? - Game Studies India Adda (Game Studies India Adda, 2020)
Video gaming is one of the most popular hobbies in the world, with the gaming industry grossing more revenue than the movie and the music industry combined. The estimated number of gamers across the whole world as of August 2020 is 2.7 billion, which is more than one-third of the world population. The benefits of gaming, as cited by numerous researchers, include a boost in confidence, improved cognitive abilities, stress relief, improved problem-solving skills, enhanced social skills among dyslexic kids, and among many others. Even though video gaming as a hobby and career is slowly getting recognition in India, majority of the population still scoff at the activity, shunning gamers and game researchers alike, citing out-of-context and sometimes even false media propaganda. The challenges faced by a typical gamer in India include lack of information, budget limitation, lack of support from parents and teachers when it comes to teenage gamers, and the overall lack of gaming as a mainstream culture among countrymen. As for someone who wants to pursue Game Studies, there is currently little to no provision for that due to the tightly knit education system in the country and the utter lack of educational institutes offering courses on game studies. We go on to further discuss all of the above challenges and experiences faced by a gamer or someone who wants to pursue game studies in India, in our detailed talk that is scheduled on November 21, 2020.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

First Person Encounters #1: A Game Studies India Adda Podcast - Game Studies India Adda (2020)
The First Podcast in a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Gaming Cultures and Place in Asia-Pacific - Hjorth, Larissa; Chan, Dean (Routledge, 2009)
This collection explores the relationship between digital gaming and its cultural context by focusing on the burgeoning Asia-Pacific region. Encompassing key locations for global gaming production and consumption such as Japan, China, and South Korea, as well as increasingly significant sites including Australia and Singapore, the region provides divergent examples of the role of gaming as a socio-cultural phenomenon. Drawing from micro ethnographic studies of specific games and gaming locales to macro political economy analyses of techno-nationalisms and trans-cultural flows, this collection provides an interdisciplinary model for thinking through the politics of gaming production, representation, and consumption in the region.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé